Collaborative Parking Management in Constanta: The Role of Public Policies and Citizen Participation - Tasențe, Tănase; Stan, Mari-Isabella (Technium Social Sciences Journal, 2023)
This research focuses on Collaborative Parking Management in Constanta, Romania, examining the role of public policies and citizen participation in improving the availability and quality of parking spaces. The study's general objective is to evaluate citizens' perceptions of parking spaces in Constanta and identify potential solutions to improve the current situation. To achieve this, the study outlines six specific objectives, including analyzing parking space availability, evaluating the quality of parking infrastructure, examining opinions on parking regulation and costs, investigating the impact on the environment, assessing the influence on vehicle and pedestrian safety, and identifying solutions for parking management improvement. The research tool utilized for this study was an online questionnaire, which included six dimensions related to parking space availability and quality, regulation and costs, impact on the environment, and safety, as well as a section for participants to make recommendations. This study aims to provide insight into the current state of parking in Constanta and offer practical solutions for improving the parking situation through collaboration between citizens and policymakers.